2022
DOI: 10.3390/mi13050659
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Macroscopic and Microstructural Features of Metallic Coating Created by Pulsed Laser Material Deposition

Abstract: Owing to the unparalleled advantages in repairing of high value-add component with big size, fabricating of functionally graded material, and cladding to enhance the surface properties of parts, the laser material deposition (LMD) is widely used. Compared to the continuous wave (CW) laser, the controllability of the laser energy would be improved and the temperature history would be different under the condition of pulse wave (PW) laser through changing the pulse parameters, such as duty cycle and pulse freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 107 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…To enhance their corrosion resistance, surface modifications can be applied to alter the surface chemistry. One surface modification technique that has demonstrated its capacity for improving the corrosion resistance of MASS is ion implantation [20,177]. For example, nitrogen ions can be implanted into the surface layer of the material to form a nitrogen-enriched layer that is highly resistant to corrosion [178].…”
Section: Corrosion Resistancementioning
confidence: 99%
“…To enhance their corrosion resistance, surface modifications can be applied to alter the surface chemistry. One surface modification technique that has demonstrated its capacity for improving the corrosion resistance of MASS is ion implantation [20,177]. For example, nitrogen ions can be implanted into the surface layer of the material to form a nitrogen-enriched layer that is highly resistant to corrosion [178].…”
Section: Corrosion Resistancementioning
confidence: 99%
“…Due to all these above-mentioned factors being presented, the thermal reversion treatment takes place at the mentioned point. In this sense, by reducing the laser power by at least a factor of two, the input of the laser energy is around 80 mW, which is not in the threshold range to produce a phase transformation from γ-to α -phase [32][33][34]. As a direct consequence of this effect, the resulting superficial HV does not increase.…”
Section: Superficial Hardness Evolutionmentioning
confidence: 99%
“…Wang et al [10] reported a review of the macroscopic and microstructural features of metallic coating created by pulse-wave (PW) laser material deposition (LMD). The research status of temperature field simulation, surface quality and microstructural features, including microstructures, microhardness, residual stress and cracking, as well as corrosion behavior of metallic coating created by pulsed-laser material deposition, were reviewed.…”
Section: Processes Of Laser Additive Manufacturing In This Special Issuementioning
confidence: 99%